Mandibulary dental arch form differences between level four polynomial method and pentamorphic pattern for normal occlusion sample - Yuliana, Y.; Thahar, Bergman; Salim, Jono; Mardiati, Endah (Padjadjaran Journal of Dentistry, 2011)
The aim of an orthodontic treatment is to achieve aesthetic, dental health and the surrounding tissues, occlusal functional relationship, and stability. The success of an orthodontic treatment is influenced by many factors, such as diagnosis and treatment plan. In order to do a diagnosis and a treatment plan, medical record, clinical examination, radiographic examination, extra oral and intra oral photos, as well as study model analysis are needed. The purpose of this study was to evaluate the differences in dental arch form between level four polynomial and pentamorphic arch form and to determine which one is best suitable for normal occlusion sample. This analytic comparative study was conducted at Faculty of Dentistry Universitas Padjadjaran on 13 models by comparing the dental arch form using the level four polynomial method based on mathematical calculations, the pattern of the pentamorphic arch and mandibular normal occlusion as a control. The results obtained were tested using statistical analysis T student test. The results indicate a significant difference both in the form of level four polynomial method and pentamorphic arch form when compared with mandibular normal occlusion dental arch form. Level four polynomial fits better, compare to pentamorphic arch form.